With more nobility than the entire world has had: Ventura Travada's vindicatio indianorum (c. 1752) and the topic of "colonial racism" in Peru - Sánchez Martínez, César Félix (2011)
The reduction of the complexities of Andean subjectivity in Viceregal Peru to Modern ideological constructions could lead to anachronisms and it’s a constant risk in Intellectual and Mediatic spaces of reflection. In this article, we will look for these complexities through the study of the work of an Andean cleric, father Buenaventura Fernández de Córdoba y Peredo (1695-1758), also known as Ventura Travada, autor of El Suelo de Arequipa convertido en Cielo (c. 1752). We will look also for the value and consistency of the so called «Colonial Racism», a common ideological topic.